IMPLEMENTATION OF VISIONARY LEADERSHIP IN FORMING THE EXCELLENT POSITION OF THE INDONESIAN NATIONAL POLICE (POLRI) IN THE METROPOLITAN POLICE REGION - Muh. Mahdi Heaveny N.; Surya Nita; Yopik Gani (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
The visionary leadership style focuses on school principals' ability to create a forward-thinking vision for the school, driving change and setting the organization's direction. This scientific article proposes implementing visionary leadership to shape the Indonesian National Police (Polri) excellence in the Jakarta Metropolitan Police. The study uses a qualitative approach with analytical descriptive to provide a detailed overview. Primary and secondary data, collected through observation, interviews, and document studies, are used. The author validates the data using triangulation techniques. The research findings reveal that visionary leadership is performance-oriented, with a focus on designing a future vision. It encompasses three characteristics: (1) "Leading by example in front"; (2) "Creating opportunities for initiative in the middle"; and (3) "Providing support from behind." The current leadership style in the Jakarta Metropolitan Police has several weaknesses, including a military influence, an unclear vision, a lack of organizational orientation, weak managerial skills, a gap between top and low-level managers, a lavish lifestyle, and disregard for the environment. One indicator is the high number of violations by officers in 2022, including 26 disciplinary violations and 215 ethical code violations. Strategies for implementing visionary leadership in the Jakarta Metropolitan Police include defining the organizational vision, translating it into a mission, creating strategies, conducting evaluations, developing work plans, demonstrating commitment and integrity, upholding leadership ethics, and making prompt and accurate decisions.